Development of Madura Herbal Medicine Database System using Software Development Model of Fast Collaboration Competencies Model - Yusuf, Muhammad; Kautsar Sophan, Moch; Agustiono, Wahyudi; Irhamni, Firli; Syarief, Mohammad; Rahmanita, Eza (Jurnal Teknokes, 2025)
Herbal medicine is an original Indonesian product made with natural ingredients. Furthermore, Madura also offers many herbal medicines, such as strong and healthy for men and women after giving birth, beauty and body maintenance, cold, smooth breast milk, and others. Various research and development projects worldwide on technology related to traditional or herbal medicine exist. However, a limited database contains data and information about Madura Herbal medicine. This research aims to develop the Madura Herbal Medicine Database System using the Fast Collaboration Competencies (FCC) to facilitate fast and collaborative teamwork as well as based on competencies. The FCC is a software development method that manages and collaborates across diverse skills, expertise, and competencies. The Madura Herbal Medicine database system was developed using a use case diagram, system architecture, and database design. After that, we created a mock-up or prototype. Then, we implemented the system using PHP Rad and a Decision Tree. Moreover, it provides a Madura Herbal Medicine Database system for research, marketing, and production mapping. The research result is a  Madura herbal database system that contains herbal medicine data from Bangkalan, Sampang, Pamekasan, and Sumenep. The Madura herbal database system is essential for buyers, producers, marketers, sales personnel, researchers, and other institutions to provide herbal medicine information and support decision-making. Those four cities are located in Madura. Those two websites have combined through a landing page and API. Therefore, two databases can access each other's data. The Madura Herbal Medicine system can apply Fuzzy KNN and Open data for herbal medicine in the future.